Implementasi Penyembunyian Pesan Pada Citra Digital Dengan Menggabungkan Algoritma Hill Cipher Dan Metode Least Significant Bit (LSB) - Jane Irma Sari; Sulindawaty M.KOM; Hengki Tamando Sihotang (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
The rapid development of technology in the current era, hiding undisclosed messages from irresponsible people or who can access the message required a way to hide the message. One way of concealment of messages in transmission is to change the data to be not understood by encryption and insertion using cryptography and steganography techniques. The purpose of this thesis is to produce an application that can maintain and provide layered security without reducing or damaging text messages on digital images to be sent. This application is built using Hill Cipher algorithm and Least Significant Bit method, this algorithm is one of symmetric key algorithm which has some advantages in data encryption. Hill Chiper algorithm uses an mx m sized matrix as the key for encryption and decryption. While steganography is done by replacing the last bits of the image with text message bits. The result of this research is an application that can do the process of encode and decode digital image with bitmap format